FmRα analysis: Rapid and direct estimation of relaxation and kinetic parameters from dynamic nuclear polarization time courses. Issue 6 (2nd July 2014) - Pagès, Guilhem; Kuchel, Philip W.
<x xml:space="preserve">Abstract</x> Purpose To introduce a direct method for estimating relaxation and kinetic parameter values from rapid dissolution dynamic nuclear polarization (RD‐DNP) NMR time courses. Theory and Methods The analysis relied on a kinetic model that is often used to analyze data in these studies—a unidirectional (bio)chemical reaction with rate constant k1, coupled to longitudinal relaxation of the magnetization of substrate and product that is characterized by the time constant T1. The latter value was estimated from the width of the product curve (peak) at the height α relative to the maximum height. We showed α ∼ 0.8 under most conditions, so we measured the interval between the falling and rising parts of the curve at the relative height 0.8. We called this the "fall‐minus‐rise time at height α, " or FmRα, and found that FmR0.8 ∼ T1. The ratio β = (product signal/substrate signal) when the product is maximal was shown to be equal to k1T1. Therefore, k1 = β/FmR0.8. Results FmRα analysis was demonstrated with 13C NMR RD‐DNP data recorded from hemolysates and from previously published data. Conclusion FmRα analysis enables immediate estimates of kinetic and relaxation parameters from 13C NMR RD‐DNP data. The values can be used as initial estimates in more extensive computer‐based data‐regression analysis. Magn Reson Med 73:2075–2080, 2015. © 2014 Wiley Periodicals, Inc.